Preparation of N- and C-Functionally-Substituted Glutarimides: A Review - Trukhanova, Yulia A.; Chernov, Nikita M.; Kuvaeva, Elena V.; Yakovlev, Igor P. (Synthesis, 2023)
Six-membered heterocyclic systems such as glutarimides are widely used in medicinal chemistry. The glutarimide skeleton is found in many commercially available pharmaceuticals due to a wide range of bioactivity. The preparation of C,N-highly functionalized glutarimides is an important topic in modern organic synthesis, since it reveals the ability to build a more complex system and thus expands the range of various drugs. This review describes approaches to the synthesis of N- and C-functionally-substituted glutarimides presented in the literature from 2005 to 2022. Options for the enantioselective synthesis of spiroglutarimides, the use of organocatalysis in the synthesis of glutarimides, and optimization of the synthesis of already known pharmaceuticals are described.1 Introduction2 Michael Addition2.1 Preparation of Glutarimides from Substituted Acrylamides and 1,3-Bielectrophiles2.2 Preparation of Glutarimides by the Reaction of Acetamide and α,β-Unsaturated Carbonyl Compounds2.2.1 Preparation of Glutarimides by the Reaction of Acetamide Derivatives and Acrolein Derivatives2.2.2 Preparation of Spiroglutarimides by the Reaction of Acetamide Derivatives and Bromacrolein Derivatives2.2.3 Preparation of Spiroglutarimides by the Reaction of Acetamide Derivatives and Acryloyl Cyanide Derivatives2.2.4 Preparation of Substituted Glutarimides Using Ytterbium Salts2.3 Michael Addition/Intramolecular Transacylation2.4 Preparation of Glutarimides from Baylis–Hillman Adducts3 Multicomponent Reactions4 Conclusion
Keywords: glutarimides; Michael addition; multicomponent reactions; enantioselectivity; organocatalysis